2008
DOI: 10.2308/aud.2008.27.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Moods on Auditors’ Inventory Valuation Decisions

Abstract: This paper investigates the effect of different mood states-specifically positive, neutral, and negative mood-on inventory valuation decisions. Psychological research suggests that different mood states can lead to different professional judgments in the performance of an ambiguous task. Compared with neutral-and negativemood individuals, positive-mood individuals have the lowest consensus and make the least conservative judgment ͑i.e., the highest inventory valuation͒, and negative-mood individuals have the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 36 publications
(18 reference statements)
4
63
2
Order By: Relevance
“…While moods can impact a decision or behavior (Chung et al. ), emotions are the results of a decision or behavior.…”
mentioning
confidence: 99%
“…While moods can impact a decision or behavior (Chung et al. ), emotions are the results of a decision or behavior.…”
mentioning
confidence: 99%
“…Mood is a state of mind or feeling that is task‐irrelevant, yet it could impact auditor judgment. Chung, Cohen, and Monroe () explore whether auditors in a positive mood condition exhibit lower consensus and less conservatism relative to auditors in a negative mood condition. They find that positive‐mood participants' approach to decision‐making results in the lowest judgment consensus when compared with the neutral and negative‐mood participants.…”
Section: Literature Review By Audit Taskmentioning
confidence: 99%
“…Birnberg (2011), observed that in the last decades psychologists, experimental economists and accountants have begun to examine the role of the decision maker's emotional state (affect) on the decision process. Thus, Chung et al (2008) analyzed auditors' behavior making inventory valuation decisions and found that mood state affects the degree of conservatism in the audit mission. Hence, the author highlighted that auditors in a positive mood are less conservative than those in a negative mood.…”
Section: Optimism and Accounting Professionals' Judgmentmentioning
confidence: 99%